Alcohol and tobacco use and risk of multiple myeloma: A case‐control study. Issue 1 (10th November 2021) - Cheah, Simon; Bassett, Julie K.; Bruinsma, Fiona J.; Cozen, Wendy; Hopper, John L.; Jayasekara, Harindra; Joshua, Douglas; MacInnis, Robert J.; Prince, H. Miles; Vajdic, Claire M.; van Leeuwen, Marina T.; Doo, Nicole Wong; et al.
Abstract: Multiple myeloma (MM) is the second most common hematological cancer and causes significant mortality and morbidity. Knowledge regarding modifiable risk factors for MM remains limited. This analysis of an Australian population‐based case–control family study investigates whether smoking or alcohol consumption is associated with risk of MM and related diseases. Incident cases ( n  = 789) of MM were recruited via cancer registries in Victoria and New South Wales. Controls ( n  = 1, 113) were either family members of cases ( n  = 696) or controls recruited for a similarly designed study of renal cancers ( n  = 417). Adjusted odds ratios (OR) and 95% confidence intervals (CI) were estimated using unconditional multivariable logistic regression. Heavy intake (>20 g ethanol/day) of alcohol had a lower risk of MM compared with nondrinkers (OR = 0.68, 95% CI: 0.50–0.93), and there was an inverse dose–response relationship for average daily alcohol intake (OR per 10 g ethanol per day = 0.92, 95% CI: 0.86–0.99); there was no evidence of an interaction with sex. There was no evidence of an association with MM risk for smoking‐related exposures ( p  > 0.18). The associations between smoking and alcohol with MM are similar to those with non‐Hodgkin lymphoma. Further research into potential underlying mechanisms is warranted.